BENEFITS OF IMPROVED TEACHING METHODOLOGY FOR TEACHING NUCLEAR PHYSICS SECTIONS IN UNIVERSITIES BASED ON INNOVATIVE TECHNOLOGIES - Yusupov Dilmurod Abdurashidovich (Scholar Express Journal, 2023)
This paper proposes an improved methodology for teaching nuclear physics sections using computer technology, based on modern scientific achievements and innovative technologies. The results of experimental work presented in the article show that the use of innovative technologies in the form of visual demonstration tools effectively form the modern scientific worldview of students. Also, based on an analysis of the advantages and disadvantages of all types of energy sources, an analytical table was proposed that clearly shows the priority of modern nuclear energy sources and their high level of safety
Keywords: Modern technological devices; mass and energy; computer technology; innovative technologies